Livestock Farmers’ Perception on Animal Husbandry Services Rendered Under Corporate Social Responsibility (CSR) - Verma, Adesh Kumar; Chander, Mahesh; Kumar, Sanjay; Verma, MR; Kannadhasan, MS (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The Animal Husbandry sector receives only 12 percent of the total public expenditure on agriculture and allied areas resulting inunderperformance of the sector. However, companies are offering different animal husbandry services under their corporate socialresponsibility (CSR) programs abiding Section 135(1) of Companies Act 2013. The present study was carried out to assess the perceptionof livestock farmers on the availability and effectiveness of animal husbandry services rendered under CSR activities. A total of 120livestock farmers, each with a minimum one adult dairy animal was selected from the villages adopted by the selected companies fordelivering CSR activities. Data were collected using a well-structured and pre-tested interview schedule through personal interviewswith the respondents and analyzed appropriately to reveal the perception of livestock farmers about the availability and effectivenessof different CSR services. Most of the respondents perceived that extension, production, healthcare, and marketing services wereoccasionally available with average effectiveness due to the efficiency of services offered through CSR activities. Further, they perceivedthat the rarely available credit service had poor effectiveness. Healthcare service was the most preferred service in terms of availabilityand effectiveness, while credit service was the least preferred both in terms of availability and effectiveness.
Keywords: Animal husbandry service,; CSR activities; , Livestock farmers; Perception.